PENGARUH MODEL PROBLEM BASED LEARNING (PBL) TERHADAP KEMAMPUAN BERPIKIR KRITIS DAN PENINGKATAN HASIL BELAJAR KOGNITIF SISWA PADA MATERI SISTEM GERAK PADA MANUSIA DI KELAS VIII SMP NEGERI 43 MALUKU TENGAH - Arini, Ine; Tuapattinaya, Prelly Marsel Jolanda; Romuty, Theofany (Program Studi Pendidikan Biologi FKIP Unpatti, 2024)
Background: Problem Based Learning (PBL) is a teaching approach that provides challenges for students to find solutions to real world (open) problems individually and in groups. Problem Based Learning (PBL) was developed to help students solve problems and intellectual skills and give students the opportunity to be responsible for the independent learning process while developing their ability to solve problems and requiring students to have curiosity and make students more active in the learning process.. Methods: The data analysis used is normality, homogeneity and hypothesis testing. Results: The results showed that the average posttest score in the experimental class was 70,00 with a standard deviation of 11,79, the average posttest score in the control class was 63,56 with a standard deviation of 7,83. Conclusion: The problem based learning (PBL) model influences critical thinking skills and student learning outcomes.